Population Pharmacokinetics of CMAB008 (an Infliximab Biosimilar) and Remicade® in Healthy Subjects and Patients with Moderately to Severely Active Rheumatoid Arthritis - Su, Yin; Li, Jing; Wang, Chenguang; Zhang, Xunmin; Hou, Sheng; Guo, Huaizu; Deng, Chenhui; Ou, Lun; Wang, Jinwei (Advances in therapy, 2023)
Introduction CMAB008 is a monoclonal antibody developed as a biosimilar to infliximab (Remicade ® , Janssen). The pharmacokinetic characteristics of CMAB008 and Remicade ® in healthy subjects and patients with moderately to severely active rheumatoid arthritis (RA) were investigated using a population modeling approach, and the pharmacokinetic similarity of CMAB008 to Remicade ® was assessed. Methods The population pharmacokinetic model was developed on the basis of intensive pharmacokinetic data from a phase 1 study in healthy male subjects and combined intensive and sparse pharmacokinetic data from a phase 3 study in patients with RA. Results A two-compartment model with first-order elimination adequately described CMAB008 and Remicade ® concentration data in healthy subjects and patients with RA. The analysis of covariates identified anti-drug antibody (ADA), neutralizing antibody (NAB), real-time body weight (BWT), and real-time albumin (ALB) as significant covariates on clearance, and BWT was also a significant covariate for the central volume of distribution. The treatment type (CMAB008 versus Remicade ® ) and the study population (healthy subjects versus patients with RA) were not identified as significant covariates on the pharmacokinetics of infliximab, demonstrating pharmacokinetic similarity between CMAB008 and Remicade ® in both study populations. The effect of BWT and ALB changes on exposures to infliximab was within the acceptable range, suggesting that the 3 mg/kg regimen is appropriate in clinical practice for patients with RA and BTW and ALB distribution within the range evaluated in the current analysis. Conclusions The pharmacokinetic characteristics were similar between CMAB008 and Remicade ® in healthy subjects and patients with RA. CMAB008 can be considered bioequivalent to Remicade ® . Clinical Trial Registration ClinicalTrials.gov identifiers NCT04779892, NCT03478111.